Comprehensive Genetic Testing for Coexisting Marfan and Loeys-Dietz Syndromes in Hereditary Thoracic Aortic Disease - Yoshida, Shohei; Tada, Hayato; Goten, Chiaki; Okada, Hirofumi; Sakata, Kenji; Takamura, Masayuki (JACC. Case reports, 2024)
Hereditary thoracic aortic disease (HTAD) is a rare heritable condition with several subtypes, including Marfan syndrome (MFS), vascular Ehlers-Danlos syndrome, and Loeys-Dietz syndrome (LDS). Although MFS is the most common type of HTAD caused by mutations in FBN1, differentiation from other conditions such as LDS is crucial due to the varying clinical courses. We report the case of a family history of early-onset ascending aortic dissection initially diagnosed as MFS based on a pathogenic variant of FBN1. However, comprehensive genetic testing using next-generation sequencing and array-comparative genomic hybridization revealed a copy number variation (a large deletion) in SMAD3, resulting in a diagnosis of the coexistence of MFS and LDS. These results significantly altered the screening and follow-up strategies. This case highlights the importance of comprehensive genetic testing, not only for assessing single nucleotide polymorphisms but also for evaluating copy number variations to ensure accurate differentiation and management of HTAD. [Display omitted]